2014
DOI: 10.1186/s13052-014-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abdomen massage for prevention of feeding intolerance in preterm infants

Abstract: BackgroundThe aim of this study was to evaluate the efficacy of abdominal massage on feeding tolerance in stable preterm infants fed minimal enteral nutrition.MethodsThe study was conducted on a control-grouped pre-test, post-test quasi-experimental design at the neonatal intensive care unit of a university hospital in Turkey between March and July 2012. Abdominal massage was applied to the massage group subjects for 15 minutes, 2 times daily, before the subject was fed starting in the 5-day study period.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 24 publications
7
48
4
4
Order By: Relevance
“…On studying the premature neonates' weight at discharge, more than half of them gained from 150-200 gms after applying massage therapy, this result was in agreement with Golchin M et al (2010) and Tekgündüz K et al (2014) [8,30] who mentioned that weight gain is the most consistent indicator which is associated with massage therapy in neonates. Also, stable 28-34 weeks neonates whom were massaged for five days, three times/day by a well-trained nurse, had significantly increase their weight than those weren't massaged.…”
Section: Discussionsupporting
confidence: 85%
“…On studying the premature neonates' weight at discharge, more than half of them gained from 150-200 gms after applying massage therapy, this result was in agreement with Golchin M et al (2010) and Tekgündüz K et al (2014) [8,30] who mentioned that weight gain is the most consistent indicator which is associated with massage therapy in neonates. Also, stable 28-34 weeks neonates whom were massaged for five days, three times/day by a well-trained nurse, had significantly increase their weight than those weren't massaged.…”
Section: Discussionsupporting
confidence: 85%
“…Other conditions associated with prematurity that were found in the recent literature on preterm newborn massage include feeding intolerance, jaundice (hyperbilirubinemia) and brain injury. In a quasi-experimental design study on the prevention of feeding intolerance in preterm newborns, abdominal massage was applied to the newborns for 15 minutes twice daily just before feedings for a five day study period (Tekgunduz, Gurol, Apay, & Caner, 2014). By the last day of the study the massage therapy group versus the control group showed greater daily weight gain, less frequent vomiting, less gastric residual volume and lower abdominal circumference (less abdominal distension).…”
Section: Preterm Newborn Massage Therapy Effectsmentioning
confidence: 99%
“…A total of 1035 preterms have been included (N= 593 in experimental group and N=442 in control group). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Herewith the analyzed studies, the ex-Serap ÖZDEMİR et al…”
Section: Resultsmentioning
confidence: 99%
“…The massage implementation was found to possess positive effect on weight gain. 20,22,[24][25][26][27][28][29][30][31][32][33][34][35][36] whereas there were no sig-nificant effects on weight gain. 21,37,38 Evidence-based care guidelines for preterm infant massage is defined gastric motility and weight gain among preterm infants.…”
Section: Resultsmentioning
confidence: 99%